THE IMPACT OF U.S. INTERNATIONAL MILITARY CAMPAIGN â€œWAR ON TERRORâ€ ON THE PAKISTANI CIVILIANS (A CASE STUDY : DRONES ATTACK IN PAKISTAN 2004 â€“ 2014) - Nyssa Nastasia (HI 16 UMY 047, 2016)
*47 This researched on the impacts of U.S. International Military Campaign towards the Pakistani civilians with the case study of drones strikes in Pakistan from the year 2004 until 2014 aims to find out the impacts of drones strikes in Pakistan with regard to the humanity and psychological aspect of the Pakistani civilians. As we know, the impacts of drones strikes in Pakistan resulted in the death of many Pakistani civilians.This researched uses the qualitative method from the data retrieved from secondary sources such as books, news and journals. The result of the researched shows that not only the lives of the Pakistani civilians are loss but their humanity aspect such as economic, health, food, community are also impacted in a negative way. The psychology of the Pakistani civilians are also effected in a negative way and this can lead to an increase in terrorist activity.